Overall Survival With Palbociclib and Aromatase Inhibitor Versus Aromatase Inhibitor Alone in Older Patients With HR+/HER2− Metastatic Breast Cancer - Adam M. Brufsky; Rickard Sandin; Stella Stergiopoulos; Connie Chen; Siddharth Karanth; Benjamin Li; Elizabeth Esterberg; Doris Makari; Sean D. Candrilli; Ravi K. Goyal; Hope S. Rugo (Cancer Medicine)
ABSTRACT Introduction Cyclin‐dependent kinase 4/6 inhibitors (CDK4/6is) in combination with endocrine therapy are the current standard of care for first‐line (1L) treatment of hormone receptor–positive and human epidermal growth factor receptor 2–negative (HR+/HER2–) metastatic breast cancer (mBC). To investigate the effectiveness of palbociclib, the first‐in‐class CDK4/6i, plus an aromatase inhibitor (AI) in older patients, we compared overall survival (OS) in a Medicare population treated with 1L palbociclib + AI versus an AI alone. Methods Patients aged ≥ 65 years who were diagnosed with de novo HR+/HER2– mBC from 2015 to 2019 were identified from the Surveillance, Epidemiology, and End Results (SEER)–linked Medicare database and were eligible if they initiated 1L palbociclib + AI or an AI alone. The primary endpoint was OS. Stabilized inverse probability of treatment weighting (sIPTW) was used to balance baseline patient characteristics. Results Of 779 eligible patients, 296 received palbociclib + AI and 483 received AI alone as 1L treatment. After sIPTW, the median follow‐up was 23.1 months with palbociclib + AI and 18.2 months with AI alone. Adjusted median OS was longer with palbociclib + AI versus AI alone (sIPTW: 37.6 vs. 25.5 months, HR = 0.73 [95% CI, 0.59–0.91]). In multivariable Cox proportional hazards regression, patients treated with palbociclib + AI versus AI alone had a 39% lower risk of death (HR = 0.61 [95% CI, 0.48–0.77]). Conclusion In routine US clinical practice, palbociclib + AI was associated with significantly prolonged OS versus AI alone in 1L treatment of patients aged ≥ 65 years with de novo HR+/HER2– mBC, adding to the growing body of evidence on the survival benefit of palbociclib + AI in this patient population. Trial Registration ClinicalTrials.gov identifier: NCT06086340